Two new species of the genus Celyphoma Emeljanov, 1971 (Hemiptera: Fulgoromorpha: Issidae) from China - Meng, Rui; Wang, Yinglun (Zootaxa, 2012)
Two new species of the genus Celyphoma Emeljanov, 1971 in the tribe Issini, C. quadrupla sp. nov. and C. bifurca sp. nov., are described and illustrated. In addition, the male and female reproductive systems of C. quadrupla sp. nov. are described. A key to all 26 species in the genus is provided.